Antimicrobial activity of ClO2 gas against Salmonella Enteritidis on almonds. (October 2021) - Lim, Jihwan; Kim, Eungyung; Shin, Yeseul; Ryu, Jee-hoon; Kim, Hoikyung
Abstract: Nuts, including almonds, are occasionally contaminated with Salmonella spp. In this study, we used chlorine dioxide (ClO2 ) gas to inactivate S. enterica subsp. Enterica serovar Enteritidis on almonds. Almonds inoculated with a single strain of S. Enteritidis (8.95 log cfu/mL) were exposed to ClO2 gas generated from 1.0 or 1.5 mL ClO2 solution in a sealed container at 50 or 60 °C (43% relative humidity) for up to 10 h. The concentration of ClO2 gas peaked at 354–510 and 750–786 ppm within 0.5 h upon deposition of 1.0 and 1.5 mL of aqueous ClO2, respectively, and gradually decreased thereafter. Population of S . Enteritidis on almonds treated at 50 °C decreased to 1.70–2.32 log cfu/sample within 1 h of exposure to ClO2 gas and decreased to below the detection limit (1.7 log cfu/sample) at all ClO2 concentrations after 8 h. At 60 °C, the microbial population fell below the detection limit within 1 h, regardless of the volume of ClO2 solution supplied. Microbial survival on almonds treated with ClO2 gas and stored at 12 or 25 °C was observed for up to 8 weeks and the organism was not recovered from the almonds treated for 10 h and stored at 12 °C for 2–8 weeks. The lightness ( L value) and redness ( a value) of almonds treated for 10 h were not changed by ClO2 gas treatment, but yellowness ( b value) increased. Results showed that Salmonella on almonds was successfully inactivated by ClO2 gas treatment and the microbial survival did not occur during storage. Highlights: Approximately 4-log reduction in Salmonella populations occurred on almonds after gaseous ClO2 treatment for 0.5–8 h. Increasing ClO2 concentration or temperature shorten time to significantly reduce populations of S. Enteritidis on almonds. Concentration of ClO2 gas released from ClO2 solution was peaked within 0.5 h, regardless of temperature. Microbial survival did not occur on almonds treated by ClO2 gas followed by storage at 12 or 25 °C for 8 weeks.